Les succursales en droit international et européen. - Lagtati, Kamal (Université d'Auvergne Clermont-Ferrand 1, 2011)
Les succursales implantées dans un pays étranger sont plus autonomes que leurs consoeurs situées dans le même pays que la maison mère. Elles évoluent dans un environnement juridique différent et par conséquent les liens avec la maison mère sont distendus. Le tribunal de l’Etat d’accueil de la succursale est compétent et les lois de ce pays sont applicables. Toutefois, les lois du pays d’accueil ne sont pas les seules à être applicables. L’absence de personnalité juridique des succursales aura pour conséquence la sollicitation des lois de la maison mère. La cohabitation entre territorialité et extraterritorialité des lois peut donner lieu soit à des conflits soit à des situations de fraude. En l’absence de coopération entre Etats, les succursales qui sont des formes de rayonnement extérieur de la société deviennent des instruments pour pratiquer non seulement le forum shopping mais aussi le law shopping et le tax shopping.
Keywords: Agrément; Approval; Branch; Droit commercial (droit européen); Droit international économique; Extraterritoriality; Extraterritorialité; Fiscalité; Harmonisation (droit); Harmonization (law); Insolvabilité; Insolvency; Nationalisation; Nationalization; Succursale; Succursales; Tax system; Territoriality; Territorialité

The external relations of company groups in South African law : a critical comparative analysis - Stevens, Richard Arno (University of Stellenbosch, 2011)
Groups of companies are part of the realities of the modern economic system. Despite the fact that such groups often function as a single economic entity, the legal point of departure remains that each company within the group of companies is a separate juristic person. The result of this is that a creditor of a company within the group can, in principle, only enforce his claim against the company which he contracted with or which caused him harm. Should he wish to claim from the holding company or other solvent companies within the group, he would have to rely on an exception to the doctrine of separate juristic personality, viz the possibility of piercing the socalled corporate veil. This dissertation is a comparative study of the extent to which the law protects a creditor of an insolvent company within a group. The applicable laws of Australia, Germany, New Zealand, the United Kingdom and the United States of America, were investigated and compared to the South African position. The dissertation concludes that the South African legal treatment of the problem is unsatisfactory and that the law should be amended through appropriate legislation.
URI: http://hdl.handle.net/10019.1/6883
Keywords: Company groups; Creditors; South African companies; South African law

Le recours au droit des sociétés pour sauver les meubles des concubins qui se séparent ! - Bouchard, Charlaine (Revue du notariat, 2011)

Vergi Hukukunda birleşme, bölünme ve hisse değişimi işlemleri - Göktuna, Hamdi Deniz Ege (Marmara Üniversitesi, 2011)
Kurumların birleşme, bölünme, kısmi bölünme ve hisse değişimi yoluyla yeniden yapılandırılma işlemleri başta ticaret hukuku olmak üzere, rekabet hukuku, sermaye piyasası hukuku ve vergi hukuku gibi birçok hukuk dalını ilgilendiren çok disiplinli bir alandır. Ticaret hukuku, genel olarak yeniden yapılandırma işlemlerinde şirket alacaklarının ve ortaklarının haklarının korunmasını amaçlamaktayken, vergi hukuku söz konusu işlemler sonucunda ortaya çıkan kâr ile ilgilenmektedir. Yeniden yapılanma işlemlerin vergisel maliyeti, bunların önündeki en önemli engeli teşkil etmektedir. Bu sebeple, tüm hukuk sistemlerinde vergisel açıdan tarafsızlığı sağlayıcı hükümler yer almaktadır.Çalışmamızda, özellikle, üye devletler arasındaki ekonomik ilişkilerin artırılarak, ekonomik gelişmenin ve refahın sağlanması yoluyla güçlü bir topluluk yaratma amacı taşıyan Avrupa Birliği Hukuku ve Türk Hukukunda yeniden yapılandırma işlemlerinin vergisel boyutu incelenmiştir. Avrupa Birliği Mevzuatına uyum sağlama çalışmaları çerçevesinde dolaysız vergiler alanında yapılması gereken düzenlemelerden birisi de vergi kanunlarında şirketlerin bölünmesini ve hisse değişimini kolaylaştırıcı, kalıcı mahiyette hükümler getirmek olmuştur. Dolayısıyla Avrupa Birliği Birleşme mevzuatı, tam üyelik sürecindeki ülkemiz açısından önem arz etmektedir.Çalışmamızın birinci bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerinin kavramsal esasları, Kurumlar Vergisi Kanunu, Türk Ticaret Kanunu ve Yeni Türk Ticaret Kanunu ile ilgili Avrupa Birliği mevzuatı çerçevesinde ortaya konulmaya çalışılacaktır. İkinci bölümde, birleşme, bölünme, kısmi bölünme, aktif transferi ve hisse değişimine ilişkin temel Avrupa Birliği düzenlemesi olan Birleşme Direktifi, Avrupa Birliği Adalet Divanı kararları çerçevesinde incelenecektir. Son bölümde ise Türk vergi mevzuatındaki, birleşme, bölünme ve hisse değişimine ilişkin hükümler tereddütlü noktalara da değinilmek suretiyle ele alınacaktır. Sonuç bölümünde birleşme, bölünme, kısmi bölünme ve hisse değişimi müesseselerine ilişkin değerlendirmelerimize yer verilmiştir. Transactions concerning the restructuring of companies through mergers, divisions, partial divisions and exchanges of shares relate to a multi disciplinary domain, including commercial law, competition law, capital markets law and tax law. While commercial law generally aims at the protection of rights of company's creditors and shareholders, tax law is mostly interested with the profit generated through these transactions. The tax cost of restructuring transactions, constitutes the main obstacle for those. For this reason, all legal systems include provisions providing tax neutrality regarding these transactions.In this study, we have analysed the tax law dimension of restructuring transactions especially in Turkish Law and Law of European Union which aims at the creation of a strong community through the development of economic relations between member states. Within the context of harmonisation to the European Union Legislation, one of the necessary regulations concerning direct taxes has been the enactment of tax law provisions enabling the division of companies and exchanges of shares thereof. Consequently, EU Merger Legislation is of utmost importance for Turkey as a candidate state.The first chapter of this study presents the conceptual basis of the transactions in question within the context of Corporate Tax Law, Commercial Law and the New Commercial Law and EU Legislation. The second chapter examines the Merger Directive within the framework of jurisprudences of European Court of Justice. The last chapter deals with problematic issues in Turkish Tax and Commercial laws. We conclude by presenting our evaluations based on previous chapters.
Tez N° 291505
Keywords: Avrupa Birliği hukuku; Avrupa Topluluğu hukuku; Birleşmeler; Change; Corporate Tax Law; Değişim; Division of company; European Community law; European Union law; Hisse senedi devri; Hisse senetleri; Kurumlar Vergisi Kanunu; Mergers; Stock transfer; Stocks; Tax harmonisation; Tax law; Vergi hukuku; Vergi uyumlaştırması; Şirket birleşmeleri; Şirket bölünmesi

Anonim ortaklıklarda anasözleşme değişikliği - Hamamcioğlu, Esra (Ankara Üniversitesi, 2011)
Tezimizin amacı, ortaklığın anayasası niteliğinde sayılan anasözleşmedeki değişikliklerin, hangi temel esaslar dahilinde yapılabileceğini ortaya koymak, değişikliğin şekli, kapsamı, usulü, sınırları ve sonuçları konusundaki mevzuat hükümlerini, doktrin görüşleri ve uygulama sorunları ile birlikte incelemektir. Çalışmamızda, ayrı birer tez konusu yapılmış veya yapılabilecek ayrıntılar içeren, esas sermaye artırımı, sermaye azaltımı gibi özel anasözleşme değişiklikleri tek tek incelenmek yerine, tüm anasözleşme değişikliklerinde geçerli olan temel esaslar incelenmeye çalışılmış, esas sermaye artırımı ve azaltımına özgü ve genel değişikliklerden farklı olan özel düzenlemeler kapsam dışı bırakılmıştır. 1 Temmuz 2012 tarihinde yürürlüğe girecek olan Yeni Türk Ticaret Kanununun konumuzla ilgili hükümleri de 6762 Sayılı Türk Ticaret Kanunu hükümleri ile karşılaştırmalı olarak tezimizde incelenmiştir. Üç ana bölümden oluşan tezimizin ilk bölümünde anasözleşme kavramı ve hukuki niteliği üzerinde durulmuş ve Alman, İsviçre, Türk öğretisindeki görüşler doğrultusunda anasözleşmenin hukuki niteliği konusunda bir sonuca varılmaya çalışılmıştır. Anasözleşme değişikliği konusunda çıkış noktamız olan anasözleşme içeriği de yine bu bölümde TTK ve YTTK hükümleri karşılaştırmalı olarak ele alınarak incelenmiştir. İkinci bölümde, öncelikle değişiklik kavramı üzerinde durulmuş ve hangi tür değişikliklerin anasözleşme değişikliği kapsamında değerlendirilmesi gerektiği tespit edilmeye çalışılmıştır. Değişiklik usul ve şartları konusu ise, değişiklik metninin hazırlanması, gerekiyorsa Sanayi ve Ticaret Bakanlığından izin alınması, değişikliğin genel kurulda karara bağlanması, imtiyazlı paysahiplerinin onayı ile ticaret siciline tescil ve ilan alt başlıkları çerçevesinde ele alınmıştır. Çalışmamızın son bölümü anasözleşme değişikliğinin sınırları ve denetimine ayrılmıştır. Bu kapsamda özellikle vazgeçilmez ve müktesep haklarla, imtiyazlı paylardan doğan hakların anasözleşme değişikliklerine çizmiş oldukları sınırlar kanun hükümleri kapsamında tespit edilmeye çalışılmıştır. Aynı bölümde, anasözleşme değişikliğinin hükümsüzlüğü ve denetimi başlığı altında, yokluk, butlan, iptal edilebilirlik ve askıda hükümsüzlük halleri üzerinde genel hatlarıyla durulmuştur. The purpose of this thesis is to put forward the main principles through which the amendments in the main contract, considered to be the constitution of partnership, could be made and to analyze provisions of the legislation together with doctrinal views and implementation issues regarding the form, scope, procedures (mode), limits and results of amendment.In this study, rather than focusing on specific main contract amendments with details that have been or could be the subject of a separate thesis such as the increase or reduction in authorized capital, the basic principles that apply to all main contract amendments were analyzed and the arrangements specific to increase and reduction in authorized capital and special arrangements, which are different from general amendments, were left out of the scope of the study.The relevant provisions of the new Turkish Commercial Code, which will come into force on 1 July 2012, are examined in this thesis in comparison with the provisions of the Turkish Commercial Law No. 6762. This thesis is consists of three main parts. In the first part, the emphasis is on the concept of main contract and its legal attributes; and in accordance with the legal opinions stemming from the German, Swiss and Turkish doctrines the first part tries to reach a conclusion regarding the legal attributes of the main contract.The content of the main contract, which is the point of departure regarding the main contract amendment, is also analyzed in this part by means of discussing the provisions of the TCL in comparison with that of the NTCC. The second part primarily focused on the concept of amendment and sought to determine what kind of amendments should be evaluated within the scope of main contract amendment.The issue of procedures and conditions for the amendment is elaborated under the subheadings: the preparation of the text of amendment, (if necessary) the authorization from the Ministry of Industry and Commerce, the decree for the amendment in the general assembly, registration at the trade registry and promulgation with the approval of the privileged shareholders.The last part of the thesis is on the limits and supervision of main contract amendment. Within this context, this part tried to determine the limits stipulated for the main contract amendments under the provisions of the law particularly by indispensable and vested rights as well as the rights incurred from concessional shares. Within the same part, under the heading/title of invalidity of the main contract amendment the cases of absence, voidness, revocation and pending invalidity have been analyzed in general terms.
Keywords: Anonim ortaklıklar; Change; Companies; Contracts; Değişim; Incorporated companies; Sözleşmeler; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Şirketler

Définir les conflits d'intérêts - Moret-Bailly, Joël J (Recueil Dalloz, 2011)

La figure polyvalente du « Squeeze out » : réflexion à partir du droit applicable dans l'espace OHADA - Njandeu, Monique Aimé (Revue Juridique de l'Ouest, 2011)
Si la révocation du dirigeant social, mandataire social et le congédiement du salarié sont admis, peut-on concevoir qu'un associé puisse être exclu de la société dont il est membre? La qualité d'associé pésente a priori un caractère permanent que justifie son origine contractuelle. La question se pose de savoir si, dans le cadre d'une société et dans le droit OHADA, pourrait s'appliquer une sanction consistant à retirer la qualité d'associé à un membre de la société en l'en excluant, sur le fondement de l'intérêt de l'entreprise. C'est ce que l'on appelle le 'squeeze out' de l'associé, expression d'origine anglo-saxonne, consacrée en droit boursier. Il s'agit d'une opération qui s'apparente à l'offre publique de retrait obligatoire: une entreprise indemnise ses actionnaires minoritaires afin qu'ils retirent leurs titres du marché. Dans le cas du 'squeeze out', l'utilité publique aura tendance à s'exprimer au travers de l'utilité sociale. L'exclusion doit être non seulement utile, mais surtout nécessaire. La compréhension du 'squeeze out' comme sanction de celui qui, par son fait ou sa situation, compromet la relation contractuelle, doit être complétée par celle du 'squeeze out' remède, afin que la notion soit susceptible d'être admise dans l'espace OHADA (première partie); appréhendé de manière large comme une exclusion, le 'sqeeze out' est une notion concernant plusieurs disciplines juridiques. Son domaine naturel est le droit boursier, et plus largement le droit des sociétés. Ses applications débordent cependant de ce cadre étroit pour se retrouver dans d'autres domaines que l'auteur qualifie d'artificiels, tout en se limitant au droit du travail et au droit des procédures civiles (deuxième partie)
Keywords: Company law; Dismissal; Droit des sociétés; Droit du travail; International law; Labour law